1999
DOI: 10.1002/(sici)1097-0215(19990412)81:2<275::aid-ijc18>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

EB/RP gene family encodes tubulin binding proteins

Abstract: Mutations in the adenomatous polyposis coli (APC) gene are linked to the dysplastic transformation of colorectal polyps and represent an early step in the development of colorectal tumors. Ninety-four percent of all mutations result in the expression of a truncated APC protein lacking the C-terminal region. The C-terminal region of the APC protein may have a tumor suppressor function as its absence appears to be linked to the development of dysplastic lesions. Recently, we discovered and characterized a protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 22 publications
4
69
1
1
Order By: Relevance
“…APC has been shown to associate with EB1 (Su et al, 1995), a 30 kDa protein which we (Morrison et al, 1998a) and others (Berrueta et al, 1998;Juwana et al, 1999) have recently shown to be associated with microtubule tips. APC is itself a microtubule tip-associated protein (Munemitsu et al, 1994;Smith et al, 1994;NaÈ thke et al, 1996;Morrison et al, 1997), a feature ascribed to the presence of a microtubule-binding basic domain towards the Cterminus of the protein.…”
Section: Introductionmentioning
confidence: 80%
“…APC has been shown to associate with EB1 (Su et al, 1995), a 30 kDa protein which we (Morrison et al, 1998a) and others (Berrueta et al, 1998;Juwana et al, 1999) have recently shown to be associated with microtubule tips. APC is itself a microtubule tip-associated protein (Munemitsu et al, 1994;Smith et al, 1994;NaÈ thke et al, 1996;Morrison et al, 1997), a feature ascribed to the presence of a microtubule-binding basic domain towards the Cterminus of the protein.…”
Section: Introductionmentioning
confidence: 80%
“…This proposed function of KRIT1 in targeting microtubules in response to external signals is reminiscent of that of EB1, another plus end microtubule-binding protein. EB1 binds to the tumor suppressor adenomatosis polyposis coli (APC), and it has been proposed that the activity of the Wnt signaling pathway is involved in the regulation of this interaction and the consequent targeting of microtubules (37).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins homologous to EB1 have been identified in many organisms from yeast to human and have been shown to interact with MT plus-ends (6,(12)(13)(14)(15). EB1 binding to MTs is independent of APC, but APC targeting to MT plus-ends requires EB1 (16,17).…”
mentioning
confidence: 99%